Inflation Expectations of Experts and ECB Communication - Katrin Ullrich (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2007)
The communication policy of the European Central Bank attracts a lot of attention from financial markets. This paper analyses the informational content of the monthly introductory statements of the ECB president explaining interest rate decisions with regard to inflation expectations of financial market experts for the euro area from February 1999 to June 2007. Estimations are conducted for the influence of ECB communication on expectations formation besides other macroeconomic variables. As the results indicate, the indicator measuring the informational content of ECB rhetoric contributes to the explanation of inflation expectations formation.
Keywords: D84; D83; E58; E52; 330; inflation expectations formation; central bank communication; Carlson-Parkin method; survey expectations; Inflationserwartung; Finanzanalysten; Zentralbank; Staatliche Information; Informationswert; Schätzung; EU-Staaten